Analysis and Estimation of Residential Vibration Exposure from Railway Traffic in Sweden - Arnesson, Matilda (My University, 2016)
Ground-borne vibrations generated by train pass-byes a˙ect the people living close to railways in Sweden. Not since year 1990 there has been estimates made of the amount of people that are exposed to certain vibration velocities from railway traf-fic in Sweden. Furthermore there has never been any transfer factors published for the transmission of vibrations between the ground and the foundation of buildings in Sweden. By measuring ground-borne vibrations in the ground while doing mea-surements in the foundation, data for 51 buildings have been collected from which comparison of transfer factors between ground and foundation have been possible. The data have been analysed as an overall, as well as according to building size and foundation type. The transfer factor between ground and foundation of a building was found to be 0.83 as an overall mean. The majority of the transmission factors are in the range 0.7-1.1 and the transmission factor does not seem to be depen-dent on if the foundation type is suspended foundation or basement. Multi-dwelling buildings seems to have much lower transfer factor than one-dwelling buildings, but more data for Multi-dwelling buildings is needed to establish if this is statistically correct. In order to estimate the amount of people that are exposed to certain vibration velocities from railway traÿc in Sweden, almost 3 000 measurements of vibrations have been classified according to geology at the receiving building. A simple model have been made based on the attenuation of vibrations with distance and on the geology-classified data. Based on geological maps and a database of all properties close to railways, the total number of exposed individuals in Sweden could be estimated. The amount of people where the rms-weighted comfort values are exceeding the vibration levels 0.4, 0.7, 1.0 and 1.4 mm/s were estimated to 54 100, 25 000, 14 200 and 7 300 people respectively. The model for estimation of exposed people could be improved by using more precise soil class information and by including the soil class under the railway in the model. The model could be used to simplify analyses of vibration exposed buildings and to make rough estimates of what vibration level that might a˙ect a building.
Keywords: Building Futures; Akustik; Building Futures; Acoustics